Effects of Pregnane X Receptor Genetic Polymorphisms on Stable Warfarin Doses. (November 2015) - Moon, Jung Yeon; Chang, Byung Chul; Lee, Kyung Eun; Bang, Jun Seok; Gwak, Hye Sun
Objective: Pregnane X receptor (PXR) is a transcriptional regulator of many drug-metabolizing enzymes including cytochrome P450 (CYP) 2C9. The objective of this study was to assess the possible association between PXR single-nucleotide polymorphisms (SNPs) and stable warfarin doses. Methods: A total of 201 patients with stable warfarin doses from the EwhA-Severance Treatment (EAST) Group of Warfarin were included in this study. The influence of genetic polymorphisms on stable warfarin doses was investigated by genotyping 11 SNPs, that is, vitamin K epoxide reductase complex 1 (VKORC1) rs9934438, CYP2C9 rs1057910, CYP4F2 rs2108622, constitutive androstane receptor (CAR) rs2501873, hepatocyte nuclear factor 4α (HNF4α) rs3212198, and PXR (rs3814055, rs1403526, rs3732357, rs3732360, rs2276707 and rs2472682). Subgroup analysis was conducted on CYP2C9 wild-type homozygote allele (AA) carriers. Results: One PXR SNP of rs2472682 (A>C) exhibited significant association with stable warfarin doses in study population and the subgroup; variant homozygote carriers required significantly lower daily doses of warfarin than those carrying wild allele by about 0.8 mg. Approximate 43.7% of overall interindividual variability in warfarin dose requirement was explained by multivariate regression model. VKORC1, CYP2C9, age, CYP4F2, PXR rs2472682, and CAR/HNF4α rs2501873/rs3212198 accounted for 29.6%, 5.9%, 3.7%, 2.3%, 1.3%, and 0.9% of the variability, respectively. PXR SNP of rs2472682 remained a significant factor in CYP2C9 wild-type homozygote carriers based on univariate and multivariate analyses. The combination of CAR/HNF4α/PXR SNPs of rs2501873/rs3212198/rs2472682 showed about 1 mg dose difference between grouped genotypes in study population and subgroup. Conclusion: Our results revealed that PXR could be a determinant of stable warfarin doses.